SENDERIZACIÓN Y SEÑALETICA DE LOS ATRACTIVOS; LA CUEVA DE PIEDRA Y LAS LAGUNAS DE CHUQUIRAGUA, DE LA PARROQUIA SAN ANTONIO DE LAS ARADAS DEL CANTÓN QUILANGA DE LA PROVINCIA DE LOJA - Contento Díaz, Luis Felipe (2016)
San Antonio de las Aradas in a parish That Quilanga canton belongs to the province of Loja, is located 96 km away, has a temperate and subtropical climate, the location of esta canton Makes this place a distinctive place Because It has a great beauty. At present there are culturally and naturally many attractions in the parish of San Antonio de las Aradas, Which Have not Been developed for tourism due to the lack of interest in the community and have not Been a diffusion of the tourist attractions on the market. This research is linked to sustainability and help educate the community and tourists Quilanga to the conservation and protection of the attractions Allowing a development opportunity From this activity and Improving quality of life. The overall objective of the research: Develop a proposal senderización and attractive signage for "Cave Rock" and "Las Lagunas de Chuquiragua" San Antonio Parish of Aradas, Quilanga Canton, Province of Loja. Were Three Specific objectives set, Which was developed as Follows: The first specific objective: "Perform a tourist diagnosis of the current situation of the attractions of the parish of San Antonio de las Aradas, Quilanga Canton, Loja Province". With it came Compliance Through the scientific method, based on the investigations of several authors; analytical method, Which made it possible to analyze the environment attractive, in order to know the state in Which, in Addition to a situational analysis of the parish Were taking as source of information the various development plans and Zoning of GAD Quilanga cantonal and parish San Antonio de las Aradas. Through direct observation technique Also attractive inventory with the help of the chips MINTUR was updated; by the fact sheet of the different attractions attractions That are Within the environment and prioritize and then a potential quality and attractive Indicate hierarchy Described by sheet; Using the technique of the interview Were Able to Obtain information from the cantonal Authorities GAD to conduct the SWOT, Which allowed collecting information Necessary for Implementing research strategies. The second specific objective: Propose senderización and attractive signage for "Cave Rock" and "Las Lagunas de Chuquiragua" San Antonio Parish of Aradas, Quilanga Canton, Loja Province, to Achieve it was esta objective perform a site survey Necessary to Establish the senderización, for it was the essential, and ARGIS 10.0 BASECAMP program Facilitated Which Obtaining a planimetric and topographic survey maps detailing the route and the area Where the signage will be Implemented, Using Global Positioning System (GPS) to Obtain the geographical coordinates of the site and place it on the agenda for Their respective development. Finally signaling points Chuquiragua Lagoons trail and footpath Stone Cave, Which lead to the different attractions, Allowing Easier access and orientation was 5 identified. Likewise signage is designed to apply the rules of sustainability of the environment and conservation awareness. The third specific objective: Socialize the Proposed signage Senderización and the residents of the parish of San Antonio de las Aradas Quilanga Canton province of Loja, This objective is Accomplished by three phases: Phase 1: Through invitation by the office, attaching the schedule of the program, Attended by Authorities and tourism providers in the canton Quilanga to give way to phase 2: presentation of the research project, the same as was done without any problem using the technique Marp in Which Were the guests aware of the investigation in the parish of San Antonio de las Aradas Where They Understood and Assessed The Importance of Being Conducted the research, it finally culminated in the Phase 3: By this stage They Learned to express suggestions Through a forum for the respective analysis, thanks to That Expressed interest in the attraction as an option Canton Quilanga development. As conclusions prioritized the paths to the attractions presented deterioration for lack of maintenance, hurting tourism growth, the proposal attractive Also assist in conservation by the community and tourists helping to raise ITS Importance locally, it will Contribute to generate traffic and sources of employment. The Proposed signage will Have a minimal environmental impact Because the signage will be made with materials friendly to the environment as wood. Recommendations Made to the respective cantonal and parish GAD Quilanga GAD of San Antonio de las Aradas, the project is Implemented senderización and signage in the area, to thereby generate benefits for the community and Contribute to the conservation and protection of attractive; With agreements in Addition to the Ministry of Tourism or SECAP for training on the maintenance and protection of trails and attractions, in Addition to training of specialized guides in the area.